2022
DOI: 10.1093/cvr/cvac008
|View full text |Cite
|
Sign up to set email alerts
|

The sympathetic nervous system exacerbates carotid body sensitivity in hypertension

Abstract: Aims The carotid bodies (CB) of spontaneously hypertensive (SH) rats exhibit hypertonicity and hyperreflexia contributing to heightened peripheral sympathetic outflow. We hypothesized that CB hyperexcitability is driven by its own sympathetic innervation. Methods and results To test this, the chemoreflex was activated (NaCN 50-100 µL, 0.04%) in SH and Wistar rats in situ before and after: 1) electrical stimulation (ES; 30 Hz,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…Increased carotid body tonic activity with heating could potentially be explained by: (1) a direct effect of temperature on the carotid body's metabolic rate via the Q 10 effect (Baron & Eyzaguirre, 1977; Eyzaguirre et al., 1983; McQueen & Eyzaguirre, 1974); (2) increased efferent sympathetic nerve activity to the carotid body, which has been shown to increase both its tonicity and sensitivity in reduced preparations (Eyzaguirre et al., 1961; Felippe et al., 2022; Gagnon et al., 2015); or (3) via an increase in systemic trueV̇CO2${\dot{V}}_{{\rm{CO}}_{\rm{2}}}$, which has been linked to carotid body activation (Forster et al., 2012; Stickland et al., 2008; Weil et al., 1972).…”
Section: Discussionmentioning
confidence: 99%
“…Increased carotid body tonic activity with heating could potentially be explained by: (1) a direct effect of temperature on the carotid body's metabolic rate via the Q 10 effect (Baron & Eyzaguirre, 1977; Eyzaguirre et al., 1983; McQueen & Eyzaguirre, 1974); (2) increased efferent sympathetic nerve activity to the carotid body, which has been shown to increase both its tonicity and sensitivity in reduced preparations (Eyzaguirre et al., 1961; Felippe et al., 2022; Gagnon et al., 2015); or (3) via an increase in systemic trueV̇CO2${\dot{V}}_{{\rm{CO}}_{\rm{2}}}$, which has been linked to carotid body activation (Forster et al., 2012; Stickland et al., 2008; Weil et al., 1972).…”
Section: Discussionmentioning
confidence: 99%
“…The post ganglionic axons of the SCG are known to innervate the CBs ( Iturriaga et al, 2016 ). Electrical stimulation of the SCG has been shown to significantly sensitize the CB chemoreflex in hypertensive and normotensive rats ( Felippe and Paton, 2021 ; Getsy et al, 2021 ; Felippe et al, 2022 ). Therefore, an increased SCG neuronal activity during the recovery of ALI, in-part, might also contribute to chemoreflex sensitization observed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…As we mentioned above, CBs not only modulate sympathetic activation but also receive innervation from both sympathetic and parasympathetic systems. Animal studies revealed that the efferent impulsation in these nerves, specifically sympathetic stimulation, influences PChS [ 62 , 63 ], which could be caused by direct stimulation or vasoconstriction causing the hypoperfusion of CBs.…”
Section: Physiology and Pathophysiology Of Peripheral Chemoreceptorsmentioning
confidence: 99%